2015
DOI: 10.1016/j.sajb.2014.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Clonal fidelity of Iris sibirica plants regenerated by somatic embryogenesis and organogenesis in leaf-base culture — RAPD and flow cytometer analyses

Abstract: Efficient protocols, safe from somaclonal variation, were developed for regeneration of Iris sibirica plants via organogenesis and somatic embryogenesis from leaf-base explants cultivated on Murashige and Skoog media supplemented with thidiazuron (TDZ, 1.0 mg/l) or 2,4-dichlorophenoxyacetic acid (2,4-D, 1.0 mg/l). The morphogenic response and callus formation efficiency differed significantly between 2,4-D (80.9%) and TDZ (67%) morphogenesis induction treatments. TDZ induced only organogenic calli, while calli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 76 publications
1
12
0
1
Order By: Relevance
“…These results are similar to those obtained by Stanišić et al (2015), who found that Iris sibirica L. plants regenerated simultaneously via organogenesis and somatic embryogenesis from a callus previously induced on a medium supplemented with 1.0 mg L -1 2,4-D. Rocha et al (2015) attributed the parallel induction of shoot organogenesis and somatic embryogenesis to specific concentrations and types of PGRs, affecting the callus culture. These authors also stressed that the manipulation of in vitro culture conditions might allow these morphogenic pathways to be induced alternatively or simultaneously.…”
Section: Resultssupporting
confidence: 89%
“…These results are similar to those obtained by Stanišić et al (2015), who found that Iris sibirica L. plants regenerated simultaneously via organogenesis and somatic embryogenesis from a callus previously induced on a medium supplemented with 1.0 mg L -1 2,4-D. Rocha et al (2015) attributed the parallel induction of shoot organogenesis and somatic embryogenesis to specific concentrations and types of PGRs, affecting the callus culture. These authors also stressed that the manipulation of in vitro culture conditions might allow these morphogenic pathways to be induced alternatively or simultaneously.…”
Section: Resultssupporting
confidence: 89%
“…A wide variety of tools are available for the detection and characterization of somaclonal variants which are primarily based on the differences in morphological traits (Pérez et al 2009, 2011; Nhut et al 2013), cytogenetical analysis for the determination of numerical and structural variation in the chromosomes (Clarindo et al 2012; Currais et al 2013; Abreu et al 2014), biochemical (Vujovic et al 2010; Kar et al 2014), molecular DNA markers (Krishna and Singh 2007; Pathak and Dhawan 2012; Hossain et al 2013; Bello-Bello et al 2014) or their combinations (Horáček et al 2013; Dey et al 2015; Stanišić et al 2015). The best test for assessing somaclonal variation is to fruit out the plants and conduct an extensive horticultural evaluation, which is unfortunately a long-term endeavor with woody fruit crops, particularly (Grosser et al 1996).…”
Section: Identification Of Variation In Tissue Culturementioning
confidence: 99%
“…It was successfully used to assess genetic stability in micropropagated Puya berteroniana through adventitious shoots [41], in various tissue culture-derived plants of Citrus limon Burm. [13], in Iris sibirica plants regenerated by somatic embryogenesis and organogenesis [42], and in regenerated plants of Eryngium planum L. performed through axillary bud proliferation [17]. Cytogenetic studies and chromosome counts can provide information about abnormal mitosis or changes in ploidy levels of plants [43].…”
Section: Discussionmentioning
confidence: 99%